The Dimensions of Being in Heidegger's Philosophy - HazhanMala Hamadameen (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
In this study, we will try to discuss the topic of "being" in Heidegger's view. Heidegger uses the concept of " Dasein" to describe the topic of "being." The topic of "being" was also important in Greek philosophy. Philosophy from the beginning, the first problem that has been researched and debated has been the problem of (being). It also appears in the first step (Thales) and his students, and continues throughout the history of philosophy. But from one stage to the next, due to the differences of opinion of the philosophers on this subject, different values will be given to the concept. For example, in the golden age of Greek philosophy (Socrates, Plato, and Aristotle), "being" takes the form of dualism, and is derived from its original form. From this point of view Heidegger raises the question of the ‘meaning of being’, which he considers forgetful and seeks his own existence. Heidegger argues that "being" does not have two distinct forms, but one that has a dimension that “Dasein” conveys. Heidegger's method, which is based on the introduction of a new study of "being" as a method based on phenomenology, establishes a fundamental ontology. In other words, Heidegger was the first philosopher to claim that being in its own right was unchallenged and cut off. That is why the attempt to return to ontology is so important. In this study, we discuss a number of different perspectives on the topic of "being" and its meanings in Heidegger's philosophy.